Loss of Heterozygosity of FCY2 Leading to the Development of Flucytosine Resistance in Candida tropicalis - Chen, Yen-Ning (American Society for Microbiology, 2011)
As fluconazole resistance becomes an emerging issue for treating infections caused by Candida tropicalis, searching for alternative becomes a prominent task. In the present study, 97 clinical isolates of C. tropicalis were tested for the susceptibilities to flucytosine (5FC) with the Etest method. Although only one isolate was resistant to 5FC, 30 susceptible isolates could produce resistant progeny after exposure to the drug. Interestingly, 22 of these 30 clinical isolates had a heterozygous G/T at the 145th position on FCY2, encoding purine-cytosine permease, whereas their progeny recovered from within the inhibitory ellipses had homozygous T/T, resulting in null alleles for both copies of the gene and produced only truncated proteins, effecting the 5FC resistance. Furthermore, we found that two major fluconazole-resistant clinical clones, diploid sequence type 98 (DST98) and DST140, had a homozygous G/G at the 145th position, and neither was able to produce 5FC-resistant progeny within the inhibitory ellipses. Hence, strains of C. tropicalis containing heterozygous alleles may develop 5FC resistance readily, whereas those with homozygous G/G wild-type alleles can be treated with 5FC. Subsequently, a combination of 5FC and another antifungal drug is applicable for treating infections of C. tropicalis.